Assisted reproductive technology in Japan: A summary report for 2017 by the Ethics Committee of the Japan Society of Obstetrics and Gynecology. (21st November 2019) - Ishihara, Osamu; Jwa, Seung Chik; Kuwahara, Akira; Katagiri, Yukiko; Kuwabara, Yoshimitsu; Hamatani, Toshio; Harada, Miyuki; Ichikawa, Tomohiko
Abstract: Purpose: The Japan Society of Obstetrics and Gynecology (JSOG) has collected cycle‐based assisted reproductive technology (ART) data in an online registry since 2007. Herein, we present the characteristics and treatment outcomes of ART cycles registered during 2017. Methods: We collected cycle‐specific information for all ART cycles implemented at participating facilities and performed descriptive analysis. Results: In total, 448, 210 treatment cycles and 56, 617 neonates (1 in 16.7 neonates born in Japan) were reported in 2017, increased from 2016; the number of initiated fresh cycles decreased for the first time ever. The mean patient age was 38.0 years (standard deviation 4.6). A total 110, 641 of 245, 205 egg retrieval cycles (45.1%) were freeze‐all cycles; fresh embryo transfer (ET) was performed in 55, 720 cycles. A total 194, 415 frozen‐thawed ET cycles were reported, resulting in 66, 881 pregnancies and 47, 807 neonates born. Single ET (SET) was performed in 81.8% of fresh transfers and 83.4% of frozen cycles, with singleton pregnancy/live birth rates of 97.5%/97.3% and 96.7%/96.6%, respectively. Conclusions: Total ART cycles and subsequent live births increased continuously in 2017, whereas the number of initiated fresh cycles decreased. SET was performed in over 80% of cases, and ET shifted from using fresh embryos to frozen ones.